The palaeoenvironmental changes in the era of Greek colonization of the northern Black Sea coast and the development of Greek settlements of the lower Dniester microregion. Preliminary research - Głuszek, Inga (Acta Archaeologica Lodziensia, 2022)
DOI: https://doi.org/10.26485/AAL/2022/68/9 The Greek colonization of the Black Sea resulted in the creation of many new settlement points placed on the entire coastline of the sea basin. One of the aspects to be recognized, both when studying the beginnings of Greek colonization in the Black Sea and in relation to the later development of the Pontic poleis, are the palaeoenvironmental conditions. It is beyond discussion that certain aspects of the natural environment, such as the topography and coastal features, influenced the choice of colonization directions, the place where the colonies were established and the development of the settlement network supporting new poleis (chora). Recognition of the palaeoenvironmental features is also significant for studying contemporary archaeological sites, influencing their characteristics created by researchers excavating particular Greek centres. The reconstruction of the northern Black Sea paleoenvironment during the Greek colonization was determined by the hypothesis of sea level fluctuation, covering the entire Black Sea basin, as part of Phanagorian Regression and Nymphaeum Transgression. These processes were to reduce sea waters in the range from 2 to 15 m below the present level of the sea and then raise them again (ca 2-3 m). However, the new research and methodology proposed in the last decade undermine the validity of such a broad approach to paleo-natural phenomena, which allegedly covered the entire Black Sea coast. The results obtained for selected areas on the eastern and western parts of the northern coast of the Black Sea call into question the theory of Phanagorian Regression. The article aims to present the problem of the reconstruction of the natural environment features of the Lower Dniester area during the formation and development of the Greek colonies in this area in the light of new achievements in the reconstruction of palaeoenvironmental features of the northern Black Sea coast.